2013
DOI: 10.5507/bp.2012.061
|View full text |Cite
|
Sign up to set email alerts
|

Occult tumour cells in peritoneal lavage are a negative prognostic factor in pancreatic cancer

Abstract: Aims. The aim of this study was to test the hypothesis that occult tumour cells in peritoneal lavage are a negative prognostic factor in pancreatic adenocarcinoma. Methods. Real-time RT-PCR analysis of CEA, EGFR and hTERT transcript levels was used to identify occult tumour cells in peritoneal lavage samples from 96 pancreatic cancer patients. Results. We found significant association between CEA expression levels in peritoneal lavage and clinical stage. We also found that EGFR transcript levels were higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Reverse transcription polymerase chain reaction (RT-PCR) analysis has been one of the most frequently used methods for identifying CTCs [ 60 , 61 ]. In real-time RT-PCR, the CTC-specific messenger ribonucleic acid (mRNA) is transcribed and amplified by PCR with fluorescent dyes to quantify the exact amount of CTC-specific mRNA in the broad dynamic range [ 62 , 63 ]. Real-time PCR is a highly sensitive method for detecting and quantifying nucleic acids that can detect a single template molecule (and thus a single CTC) among 10 7 normal blood cells [ 64 ].…”
Section: Current Enrichment and Detection Techniquesmentioning
confidence: 99%
“…Reverse transcription polymerase chain reaction (RT-PCR) analysis has been one of the most frequently used methods for identifying CTCs [ 60 , 61 ]. In real-time RT-PCR, the CTC-specific messenger ribonucleic acid (mRNA) is transcribed and amplified by PCR with fluorescent dyes to quantify the exact amount of CTC-specific mRNA in the broad dynamic range [ 62 , 63 ]. Real-time PCR is a highly sensitive method for detecting and quantifying nucleic acids that can detect a single template molecule (and thus a single CTC) among 10 7 normal blood cells [ 64 ].…”
Section: Current Enrichment and Detection Techniquesmentioning
confidence: 99%
“…). Ten studies did not meet our inclusion criteria: four studies reported on patients with metastatic or locally advanced disease , in three studies no complete data were available , two studies were not original articles and one study included patients who were already included in a more recent study . Manual search of the reference lists of the included articles did not reveal new studies.…”
Section: Resultsmentioning
confidence: 99%
“…76,77 High mutated K-ras allele frequency has been shown to be a predictor for both poor prognosis and high risk of peritoneal recurrence among PC patients who underwent radical resection. 78 The transcription products of certain epithelial-specific markers and/or tumor-associated antigens also show a promising prospect in clinical application, for instance, detection of CEA mRNA or epidermal growth factor receptor 1 mRNA in the peritoneal lavage was associated with significantly shorter OS and increased risk for disease recurrence 79 ; high expression of MUC1 mRNA in peritoneal washings was a significant risk factor for postoperative peritoneal recurrence 80 ; positive CEA mRNA was correlated with increased peritoneal recurrence rate and dismal prognosis 43,81 ; and cytokeratin-19 mRNA level in peritoneal washing had a strong relationship with advanced T stage and tumor grade. 82 Because false-positive result has been reported by studies based on qRT-PCR method, 83,84 "cocktail" probes were recommended to increase its specificity.…”
Section: Discussionmentioning
confidence: 99%